A rule-based city modeling method for supporting district protective planning. (January 2017) - Luo, Yanwen; He, Jiang; He, Yuting
Highlights: We proposed a rule-based 3D modeling method (CityEngine) for supporting urban planning. We found that CityEngine is suitable for modeling large areas at a scale of less than 1:100. We summarized the four main modeling steps of CityEngine from the viewpoint of urban planning. Our case study demonstrates how to use CityEngine to support the protective planning through batch controlling of building height, etc. We clarified the applicability of CityEngine to urban planning and city design from 3D visualization, data output, trade-offs analysis, etc. Abstract: The rule-based modeling can efficiently generate 3D city models and has a great potential in supporting urban planning and city design. Nowadays there is still lack of researches about the application of the rule-based modeling from the viewpoint of urban planning. This study aims to fill this scarcity, focused on a rule-based city modeling method (CityEngine), and discussed how to use it to generate 3D city models and support urban planning projects. In the first part, this paper briefly reviewed current researches on rule-based modeling methods, and described current applications of CityEngine (CE). In the second part of the paper, an old district located in a southern city of China was taken as the study area to discuss how to apply CE to support preparation of the protection planning in this district. In the case study, the CE-based modeling process is analyzed and can be summarized from the following aspects: (1) data preparation and processing; (2) classification of urban structure elements; (3) model generating and assigning rules; (4) model generation and modification. Finally, the applicability of CE to urban planning and city design was also discussed.